RAT PALATAL GLAND’S DUCT SYSTEM RESPONSE ON ADMINISTRATION OF METHACRYLATE - Stechenko, L.A.; Ivleva, Yu.V.; Senchakovich, Yu.V. (World of Medicine and Biology, 2015)
The use of removable acrylic prostheses causes complaints of xerostomia, the cause of which is the lack of function of the small salivary glands. The goal was to determine the dynamics of changes in the ductal system of the palatine glands of rats after administration of methacrylate. A study morphometric study found that the introduction of rats, 1% solution of methyl methacrylate is a significant decrease in the metric values - external diameter, diameter of the lumen and height of epithelial cells of the ducts of the salivary glands in the palate of all time of observation. Set change due to both direct irritant effect of 1% solution of the methyl ester of methacrylic acid to the mucosa of the glandular area of the hard palate of rats, and the changes of blood supply to the mucosa.